EFL teachers’ perception towards schema activation in English reading comprehension - A case study in the Mekong delta : - Tô, Thị Ngọc Huyền (Can Tho University, 2015)
Investigate high shoolEFL teachers' perceptions towards the role of schema activation in their students' reading comprehension ability; find out the most common instructional strategies EFL teachers use to foster schema activation in the EFL classroom, and gain insights into possible difficulties EFL teachers face when activating schemata in the reading lesson